TREATMENT AND PREVENTION OF HISTOMONIASIS IN POULTRY: A LITERATURE RIVIEW - Pereira, Domingas; Merdana, I Made; Ardana, Ida Bagus Komang (Buletin Veteriner Udayana, 2022)
Histomoniasis is a protozoan parasitic disease caused by Histomonas meleagridis. Clinical signs in histomoniasis develop 6-12 days post-infection, and are most common at 11 days post-infection, and include lethargy, emaciation, unkempt hair, yellow diarrhea, sulphur-like stools in the late stages of the disease when liver function is impaired. severe, and bile pigment is excreted through the kidneys. Lesions are observed mainly in the liver and cecum. Typical liver lesions are described as necrosis that is yellow to gray, green, or red. The size of the lesions varies widely, but is usually 1–2 cm in diameter, and may coalesce to form larger areas of necrosis. The cecum is most often enlarged bilaterally, with thickening of the cecum walls. The diagnosis can be made on the basis of clinical signs and characteristic lesions of the liver and/or cecum. A well-developed target lesion in the liver +/- cecum lesion is pathognomonic for this disease. Since no approved chemotherapy product is available for the treatment of histomoniasis, control measures are focused on prevention. There are no approved chemotherapy products available for the treatment of histomoniasis, so control measures are focused on prevention. To prevent the occurrence of histomoniasis, the best prevention that can be done is to apply good sanitation in livestock cages.